2014
DOI: 10.1002/jat.3087
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin alters secretion of interleukin 1 beta from human immune cells

Abstract: Tributyltin (TBT) has been used as a biocide in industrial applications such as wood preservation, antifouling paint, and antifungal agents. Due to its many uses, it contaminates the environment and has been found in human blood samples. Interleukin 1 beta (IL-1β) is a pro-inflammatory cytokine that promotes cell growth, tissue repair, and immune response regulation. Produced predominately by both monocytes and macrophages, IL-1β appears to increase the invasiveness of certain tumors. This study shows that TBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…In fact, inhibition of p38 caused HBCD to be more effective at increasing IFNγ secretion. Previous studies have shown that p44/42 activation by TBT is involved in TBT-induced increases in IL-1β secretion (Brown & Whalen, 2014). …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, inhibition of p38 caused HBCD to be more effective at increasing IFNγ secretion. Previous studies have shown that p44/42 activation by TBT is involved in TBT-induced increases in IL-1β secretion (Brown & Whalen, 2014). …”
Section: Discussionmentioning
confidence: 98%
“…Secretion of IFNγ (Lawrence et al, 2015), IL-1β (Brown & Whalen, 2014), and TNF-α (Hurt et al, 2013) were all affected when immune cells were exposed to the BTs tributylin (TBT) or dibutyltin (DBT). Based on these facts, it is important to examine whether the brominated flame retardant compounds, HBCD and TBBPA, have the ability to alter the secretion of interferon gamma IFNγ from human immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…TBBPA and HBCD have been shown to dysregulate secretion of interferon (IFN)-γ from human immune cells (Almughamsi and Whalen, 2015). Experiments with the environmental contaminant tributyltin have shown that it is able to alter secretion of IL-1β from human immune cells (Brown and Whalen, 2015). Thus, it is important to determine whether TBBPA and HBCD are able to alter secretion of IL-1β by immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, 5 μM TBBPA caused decreased IL-1β secretion by all three different cell preparations. A previous study examining the effect of TBT on secretion of IL-1β from immune system cells showed that TBT blocked IL-1β secretion at the highest concentration (200 nM) while causing increases in secretion at lower doses (5- 50 nM) (Brown and Whalen, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Since this interleukin is pro-inflammatory material, therefore its good in stimulation both immune responses with low toxicity, which was proved by Okemoto et al, (17) they mentioned, lipid A failed to induce activation of caspase-1, which catalyzes IL-1beta precursor processing. These results suggest that an immune response without activation of caspase-1 led to lowering toxicity of this adjuvant, also IL1beta promotes cell growth, tissue repair, and immune response regulation and have a significant role in many chronic and acute inflammatory diseases (18,19). On the other hand, the decline in its concentration for other routes …”
Section: Interleukin 1βmentioning
confidence: 93%